Prevalens Diabetis Melitus dan faktor-faktor yang berkaitan di kalangan penduduk Bukit Badong, Kuala Selangor - Adi O.; Adilah A.; Amer Hussairi M.R.; Azhar Y.; Choong C.H.; Fadzillah I.; Ida Zaliza Z.A.; Jamalludin A.R.; Lai M.W.; Lee K.M.; Megat Shiraz A.R.; Mohd Zaidi C.H.; et al. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1994)
This cross-sectional study was conducted in Kuala Selangor to determine the prevalence of diabetes mellitus and its association with risk factors such as age, sex, smoking habit, nutritional status, family history, educational level, score of diabetic knowledge and percapita income. A total of 282 samples age 18 years old and above were chosen using stratified random sampling. Data were collected by interviews using guided questionnaire, anthropometric measurement and blood glucose level using glucometer (Ames). The study showed that, the prevalence of diabetes mellitus was 8.5%. There was significant relationship (p<0.05) between diabetes mellitus with age, family history, hypertension and educational level.